Seed production in relation to fruit size of quebracho blanco (Aspidosperma quebracho-blanco) in the semiarid Chaco forest - Tálamo, Andrés; Cardozo, Silvana; Mohr, Federico (Bosque (Valdivia), 2017)
Effective management and conservation of a biological population requires knowledge of the different phases of its life cycle. We present data on seed production of quebracho blanco (white quebracho), Aspídosperma quebracho-blanco, a key tree species in the Chaco ecosystem of South America. In the southwestern sector of Copo National Park, Argentina, we recorded numbers of viable (with embryo) and non-viable (without embryo) seeds per fruit. The average fruit held 23 viable and 2 non-viable seeds (medians). Using a simple regression model we determined the relation between number of viable seeds and fruit size (width and length, respectively): bwidth = 4.9, R2 = 0.18; blength = 0.35, R2 = 0.33. The low goodness-of-fit values indicate that size is not a reliable tool for accurate predictions of the number of viable seeds per fruit. Nevertheless, given the positive slopes of the two regressions, we recommend that field workers collecting quebracho blanco seeds for regeneration select large fruits when possible. For further knowledge of this life history phase (seed production) and for estimations of the regeneration potential of quebracho blanco, we suggest that future studies focus on the variation in number of fruits produced per tree.